Freedom of Religion from the Perspective of Hadith: A Normative and Contextual Analysis Study - Suciati Fatimah; Endad Musaddad (Aslim: Journal of Education and Islamic Studies, 2025)
Freedom of religion is one of the basic principles upheld in various modern legal and thought systems, including in the discourse of human rights. In Islam, the issue of religious freedom is often debated, especially regarding how the Qur'an and the Prophet Muhammad's hadith explain and apply it. This research aims to examine the concept of religious freedom in the perspective of the Prophet's hadith by using normative and contextual approaches. This research is a qualitative study based on library research with thematic analysis method of relevant hadiths. The normative approach is used to examine the values, norms, and teachings of Islamic law contained in the hadith text. Meanwhile, the contextual approach is used to understand the social, political, and cultural background when the hadith was delivered, so that the meaning of the hadith can be interpreted as a whole and not separated from its historical reality. The results show that the Prophet Muhammad upheld the principle of religious freedom through his speech and social practices, including in the Medina Charter and interactions with non-Muslim communities. Hadiths that support the principles of tolerance, protection of non-Muslims, and prohibition of religious coercion show that Islam substantially upholds religious freedom. This study concludes that through a normative and contextual understanding of hadith, Islam can be understood as a religion that is true to itself.